Letrozole for Female Infertility - Yang, Ai-Min; Cui, Na; Sun, Yi-Fei; Hao, Gui-Min (Frontiers in Endocrinology, 2021)
Letrozole, an aromatase inhibitor that blocks estrogen synthesis by inhibiting the final step of the estrogen biosynthetic pathway, has been used in a wide range of infertility settings. It has been more than twenty years since the initial clinical trial of using letrozole for ovulation induction. In light of the accumulating clinical and basis research evidence, the efficacy and safety of letrozole have been identifying. This mini review focuses on our current knowledge of the applications and mechanisms of letrozole for female infertility and various questions put forward about how letrozole could be more effectively used